Cell fusions regulation and control - Larsson, Lars-Inge (Springer eBooks., 2011)
Cell fusions are important to fertilization, placentation, development of skeletal muscle and bone, calcium homeostasis and the immune defence system. Additionally, cell fusions participate in tissue repair and may be important to cancer development, progression and therapy. A large number of factors regulate cell fusions, including receptors and ligands, membrane domain organizing proteins, proteases, signaling molecules and fusogenic proteins that bring membranes close together. In the present volume, we interrogate what mechanisms that may be important to cell fusions in mammals and what mechanisms that may be shared with lower organisms and viruses. Additionally, the importance of cell fusions to the pathogenesis as well as treatment of diseases is addressed.